A Prospective Evaluation of the Heat Shock Protein 70 Gene Polymorphisms and the Risk of Stroke - Zee, Robert Y. L.; Bates, David; Ridker, Paul M. (Thrombosis and Haemostasis, 2002)
Genetic polymorphisms of heat shock protein 70-kD (HSP70) gene family have recently been hypothesized to be risk factors for cerebral ischemia. However, no prospective epidemiological data evaluating this gene family are available. The present investigation was conducted to examine the possible associations between the HSP70-1 nucleotide 190, HSP70-2 nucleotide 1267, and HSP70-hom nucleotide 2437 polymorphisms and the incidence of stroke in a large cohort of initially healthy men. 14916 apparently healthy men were followed over a 12-year period for incident stroke. Employing a nested case-control study design, 338 study participants who developed stroke (cases) and 338 ageand smoking-matched study participants who remained healthy during follow-up (controls) were evaluated. All observed genotype frequencies were in Hardy-Weinberg equilibrium. The allele and genotype distributions of the polymorphisms tested were similar among cases and controls, such that the relative risk of future stroke was 0.89 for HSP70-1 nucleotide 190 (95%CI = 0.70–1.12; p = 0.31), 1.13 for HSP70-2 nucleotide 1267 (95%CI = 0.90–1.42; p = 0.29); and 0.89 for HSP70-hom nucleotide 2437 (95%CI = 0.65–1.21; p = 0.45), assuming an additive model. No evidence of association was observed assuming dominant or recessive mode of inheritance. In this large, prospective study, genetic polymorphisms in the HSP70 genes were not associated with risks of future stroke. Screening for these polymorphisms is unlikely to be a useful tool for risk assessment.
Keywords: Heat shock protein 70-kD; stroke; prospective study; risk factors